Effect of Chloroethane Spray in the Treatment of Spastic Torticollis in Children and Adolescents - Kumara V. Nibhanipudi MD (SAGE Publishing, 2015)
Objective . A study to determine the efficacy of chloroethane spray compared to normal saline in the treatment of spastic torticollis in children and adolescents. Hypothesis . Chloroethane spray is more superior to normal saline for the treatment of spastic torticollis in children and adolescents in the pediatric emergency room. Design . Prospective randomized study. Setting . Urban inner-city hospital pediatric emergency department. Methods and Results . All children and adolescents (between the ages of 1 and 16 years) presenting to the author with the complaint of stiff neck were enrolled in the study. A total of 132 patients were enrolled. After complete evaluation to rule out cervical spine injury, a central neurological cause, patients were enrolled in the study. Sixty-six patients were treated with chloroethane spray to the neck and the other 66 were given normal saline as placebo. Sixty-three out of 66 patients treated with chloroethane spray achieved relief in 5 minutes as demonstrated by painless and free movement of the head and neck. No adverse effects were observed. The patients treated with placebo have no relief in 5 minutes. To test the null hypothesis that the percentages improved in the 2 groups equally, we calculated the Z statistic. The Z statistic of 24 corresponded to a P value of <.0001, whether the test is 1-sided or 2-sided. Chloroethane spray treatment was superior to placebo with a high statistical significance. Conclusion . For children and adolescents with spastic torticollis chloroethane spray was more superior to normal saline in the pediatric emergency room.